— Trans — (EAAE Annual Conference Proceedings, 2019)
To introduce ourselves first, we are a group of human beings working together only because of one hidden school — EASA ( European architecture student assembly).It works like a perfect filter. Filter for those that are looking for more than general education.Forming this vision about education was a general effort of 5 of us till the very end. Following text is not just about transdisciplinarity but about educating ourselves in communication, values, equality and daily choices. We´ve learned how to take a creative critique, how to trust each other, but mostly to understand that no one of us would make this alone.
Keywords: hands-on; unexpected spatial episodes; social encounters; contextual integration; possibilities of appropriation